Resin Type and Fiber Layer Effects on the Flexural Strength of Polymer-Jute Composites - Samudra, Ahmad Krisna Aji; Murdani, Anggit (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Natural fiber-reinforced composite materials are increasingly replacing plastics in engineering applications such as architecture, construction, and the automotive industry. Among them, jute fiber has shown potential to improve the mechanical properties of polymer composites. The advantages of natural fibers include biodegradability, renewability, and environmental friendliness. However, due to their anisotropic nature, further research is required to enhance the performance of natural fiber-reinforced composites. This study aims to evaluate the effect of fiber layer number and resin type on the flexural strength of jute fiber-reinforced polymer composites, with the goal of developing a potential replacement material for the motorcycle center body cover. Specimens were fabricated using the vacuum resin infusion process with variations of 1, 2, 3, and 4 fiber layers, and two types of resin—polyester and epoxy. The flexural strength was evaluated using a three-point bending test according to the ASTM D7264 standard. The results indicated that the highest flexural strength of 96.88 MPa was obtained in jute fiber–polyester composites with a three-layer configuration, while the lowest value of 68.27 MPa was observed in jute fiber–epoxy composites with a single-layer configuration. The superior performance of the polyester matrix is attributed to its better compatibility and interfacial bonding with jute fibers.